Textbook Evaluation for The Eleventh Grade of Vocational High School - Widuri Indah Dwi Jayanti; Maya Ulyani; Surono Surono (Journal Research of Social Science, Economics, and Management, 2021)
This study aims to analyze and evaluate the EFL Textbooks for the eleventh grade of Vocational High School. The entitle of the textbook is Forward, an English Course for Vocational Students. EFL Textbooks have become an essential thing used in foreign language teaching. The textbook is a guide for teachers in carrying out the learning and teaching process in the classroom. The textbook consists of a syllabus, methodology, and supporting materials for teaching in the school. Currently, choosing a textbook is a challenging job for EFL teachers because textbooks must be under the material to be taught in class. To evaluate the content of this textbook, the theory of Harmer has been adopted to research assessing and analyzing the textbook. Researchers want to know the strengths and weaknesses of the textbook. After implementing Harmer's theory, researchers found results that showed that textbooks were satisfactory because they were affordable, contained attractive layouts, attractive designs, and clear instructions. It conforms to the current ELT methodology, covers the four language skills, and comprises a variety of culturally appropriate topics. In addition, it has add-ons, contains additional material, and provides authentic listening material. However, teachers have succeeded in using textbooks as teaching materials and are expected to help teachers meet the learning needs of students in EFL classes.